Easy stabilization of interfacially activated lipases using heterofunctional divinyl sulfone activated-octyl agarose beads. Modulation of the immobilized enzymes by altering their nanoenvironment - de Albuquerque, Tiago L.; Rueda, Nazzoly; dos Santos, Jose C. S.; Barbosa, Oveimar; Ortiz, Claudia; Binay, Baris; Ozdemir, Ece; Goncalves, Luciana R. B.; Fernandez-Lafuente, Roberto (ELSEVIER SCI LTD, 2016)
Octyl-agarose is a support that permits the one step immobilization, stabilization and purification of lipases. However, the enzyme may be released from the support under drastic conditions. This paper describes a new heterofunctional support, octyl agarose beads activated with divinyl sulfone, that has proved to be useful to produce very stable and active biocatalysts of lipases from Candida rugosa (CRL), Rhizomucor miehei (RML) and Thermomyces lanuginosus (TLL), able to work under any reaction conditions without risking enzyme desorption. The three enzymes failed in immobilization on glyoxyl-octyl supports for different reasons. The immobilization at pH 5 permitted to keep the good properties of octyl agarose. Further incubation at pH 8 permitted to establish at least one covalent enzyme-support bond per enzyme molecule (preventing the risk of enzyme desorption), avoiding the inactivation produced at pH 10, and the final result is that all three new biocatalysts are more active than the octyl-glyoxyl counterparts and much more stable (e.g., 20 using CRL). The end of the enzyme-support reaction was achieved via blocking the vinylsulfone groups with different nucleophiles (cationic, anionic, hydrophobic, etc). This not only determined the final enzyme stability, but also the activity, selectivity and even specificity of the different immobilized preparations. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Lipase interfacial activation; Heterofunctional support; Divinyl sulfone; Enzyme hyperactivation; Enzyme stabilization; Covalent immobilization; ARTHROBACTER SP LIPASE; HYDROPHOBIC SUPPORTS; CATALYTIC-PROPERTIES; LACTULOSE PALMITATE; ENZYMATIC-SYNTHESIS; KINETIC RESOLUTION; SELECTIVITY; STABILITY; MICROENVIRONMENT; BIOCATALYSIS; Biochemistry & Molecular Biology; Biotechnology & Applied Microbiology; Engineering